Poly(ethylene-co-methacrylic acid) (EMAA) as an efficient healing agent for high performance epoxy networks using diglycidyl ether of bisphenol A (DGEBA). (1st June 2016) - Pingkarawat, K.; Dell'Olio, C.; Varley, R.J.; Mouritz, A.P.
Abstract: The use of poly(ethylene- co -methacrylic acid) (EMAA) as an efficient and repeatable thermally activated healing agent in a high performance diglycidyl ether of bis phenol A (DGEBA)/diethyl toluene diamine (DETDA) mendable epoxy composite is presented. Despite curing above the melting point of EMAA (Tm = 85 °C), healing was facilitated by incorporating a preliminary low temperature curing step of 5 h at 80 °C, prior to epoxy cure at 150 °C. Healing was subsequently shown to occur at 130 °C, 150 °C and 200 °C via a pressure delivery mechanism derived from a condensation reaction between EMAA and the residual hydroxyl groups formed during epoxy cure. Healing was repeatable over 5 healing cycles despite a gradual reduction in efficiency, while efficiency increased with increasing healing temperature. Importantly, healing was evident at 130 °C, despite the epoxy network remaining in the glassy state at this temperature (Tg = 150–158 °C). As well as creating high performance mendable composites based upon DGEBA/DETDA, EMAA particles distributed evenly on the surface of the crack plane were found to enhance mode I interlaminar fracture toughness by up to 200% for both DETDA and 4, 4 diamino diphenyl sulphone (44 DDS) systems. Graphical abstract: Highlights: Highly efficiency healing of high performance epoxy using EMAA by incorporating initial low temperature cure step. Excellent repeatability up to 5 times and also displayed healing temperatures below network Tg . Mode I interlaminar fracture toughness increased by up to 200%. Healing due to pressure delivery mechanism despite curing resin system at temperatures higher than Tm of EMAA.